90=-4x-6

Simple and best practice solution for 90=-4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=-4x-6 equation:



90=-4x-6
We move all terms to the left:
90-(-4x-6)=0
We get rid of parentheses
4x+6+90=0
We add all the numbers together, and all the variables
4x+96=0
We move all terms containing x to the left, all other terms to the right
4x=-96
x=-96/4
x=-24

See similar equations:

| 6=x^2+4x | | 4.5(x+2.5)–12.5=2(x+5)–10 | | 7n^2+67n-30=0 | | 4x^2-34x=122 | | X+0.15x=140070 | | 2x=933800 | | 40=–5k | | (X-22)/2=x-48 | | A=1/2x25x15 | | (X-23)/3=x-65 | | –9x–18=–63 | | -2+5x=4x+35 | | x-7.6=5.22 | | 75*½=xx= | | 23–(3–5r)–r=–6+3(2+3r) | | 24=1/4x+8 | | 39=0.5(h-7)h | | n(n+6)=520 | | 2x-(3-x)=15 | | k(k+1)-352.8=0 | | 14k+8=-20 | | -10=4x=x+5 | | 2u^2+4u+51=(u+6)^2 | | 2x+x5=49 | | 63=7x+x+2x+(5x+3) | | 3(3x-6)=57 | | x+4-5=25-8 | | (3x^2+2x+4)/(x-2)=0 | | 14/z=7.5 | | 5x+20=-8+2x | | x/2+50=100 | | 6/100(x)=11700 |

Equations solver categories